Microcystin-LR induced microfilament rearrangement and cell invasion by activating ERK/VASP/ezrin pathway in DU145 cells. (30th April 2022) - Zhang, Xiaowen; Yi, Xiaoyu; Zhang, Qiang; Tang, Yaqi; Lu, Yongzheng; Liu, Baojie; Pan, Zhifang; Wang, Guohui; Feng, Weiguo
Abstract: Microcystin-LR (MC-LR) is an environmental toxin that is synthesized by cyanobacteria and considered a potential human carcinogen. However, the role of MC-LR in prostate cancer progression has not been elucidated. The purpose of this study was to investigate the effect of MC-LR on prostate cancer cell invasion and its underlying mechanisms. Transwell assay was performed, and the result showed that MC-LR increased DU145 cell invasion in a concentration-dependent manner. The result of Western blot showed that MC-LR promoted ERK phosphorylation, while enhancing VASP and ezrin phosphorylation. Moreover, PD0325901 was used to verify the role of the ERK/VASP/ezrin axis in MC-LR-promoted cell invasion. The results revealed that MC-LR promoted microfilament rearrangement and cell invasion by activating the ERK/VASP/ezrin pathway in DU145 cells. Finally, in vivo assay was performed, and the result suggested that MC-LR promoted p-ERK, p-VASP and p-ezrin expression and local invasion in nude mice model. Taken together, our data proved that MC-LR induced microfilament rearrangement and cell invasion by activating the ERK/VASP/ezrin pathway in DU145 cells. Graphical abstract: Image 1 Highlights: Microcystin-LR promoted DU145 cell invasion and microfilament rearrangement. Microcystin-LR activated ERK/VASP/ezrin pathway in DU145 cells. Microcystin-LR induced microfilament rearrangement and cell invasion via ERK/VASP/ezrin pathway.